2016
DOI: 10.2108/zs150211
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Polluted with Highly Concentrated Polycyclic Aromatic Hydrocarbons Suppresses Osteoblastic Activity in the Scales of Goldfish,Carassius auratus

Abstract: We have developed an original in vitro bioassay using teleost scale that has osteoclasts, osteoblasts, and bone matrix as each marker: alkaline phosphatase (ALP) for osteoblasts and tartrate-resistant acid phosphatase (TRAP) for osteoclasts. Using this scale in vitro bioassay, we examined the effects of seawater polluted with highly concentrated polycyclic aromatic hydrocarbons (PAHs) and nitro-polycyclic aromatic hydrocarbons (NPAHs) on osteoblastic and osteoclastic activities in the present study. Polluted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…At both sites, crude oil is often contained in the ballast water thrown away by ships, and the marine pollution of the Mediterranean Sea coast and the Suez Canal worsens even if there is no ship or oil tanker accident. We have reported that the concentrations of PAHs, including the PAHs shown in Figure 1, in these areas (Suez Canal: 992.56 ng/L; Alexandria port: 1364.59 ng/L) were remarkably high, around 100 times that of the Sea of Japan [95]. Furthermore, we demonstrated that they were more likely caused by PAHs included in crude oil [95].…”
Section: Toxicity Of Pahs On the Bone Metabolism Of Fishmentioning
confidence: 53%
See 1 more Smart Citation
“…At both sites, crude oil is often contained in the ballast water thrown away by ships, and the marine pollution of the Mediterranean Sea coast and the Suez Canal worsens even if there is no ship or oil tanker accident. We have reported that the concentrations of PAHs, including the PAHs shown in Figure 1, in these areas (Suez Canal: 992.56 ng/L; Alexandria port: 1364.59 ng/L) were remarkably high, around 100 times that of the Sea of Japan [95]. Furthermore, we demonstrated that they were more likely caused by PAHs included in crude oil [95].…”
Section: Toxicity Of Pahs On the Bone Metabolism Of Fishmentioning
confidence: 53%
“…We have reported that the concentrations of PAHs, including the PAHs shown in Figure 1, in these areas (Suez Canal: 992.56 ng/L; Alexandria port: 1364.59 ng/L) were remarkably high, around 100 times that of the Sea of Japan [95]. Furthermore, we demonstrated that they were more likely caused by PAHs included in crude oil [95]. Each sample of polluted seawater was added into culture medium at dilution rates of 50, 100, and 500 times and incubated with goldfish scales for 6 h. Thereafter, ALP and TRAP activities in the scales of goldfish were measured.…”
Section: Toxicity Of Pahs On the Bone Metabolism Of Fishmentioning
confidence: 91%
“…In the present study, we found that a low concentration of BaA has toxicity for the bone and liver of nibbler fish (marine teleost). As highly polluted seawater in the natural environment included BaA [18], we call for the prevention of PAH pollution.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that BaA may affect liver diseases in addition to bone diseases. As BaA is included in highly polluted seawater [18], we should emphasize the prevention of aquatic PAH pollution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation